Identification of the urinary metabolites of glionitrin A in rats using ultra-performance liquid chromatography combined with quadrupole time-of-flight mass spectrometry - Lee, Soo Hyun; Yang, Hyun Ok; Kwon, Hak Cheol; Jung, Byung Hwa (ELSEVIER, 2012)
Glionitrin A (GN A) is a new diketopiperazine disulfide with an aromatic nitro group, which is isolated from the coculture of an Aspergillus fumigatus fungal strain and a Sphingomonas bacterial strain. After intravenous administration of GN A in rats, 13 urinary metabolites of GN A were identified using ultra-performance liquid chromatography/quadrupole time-of-flight mass spectroscopy (UPLC-QTOP-MS) analysis in conjunction with data processing programs such as MetaboLynx (TM) and MassFragnent (TM). Reduction, nitro-reduction and hydration were the primary metabolic processes affecting GN A in vivo, followed by demethylation or oxidative deamination to alcohol, as well as cysteine, glycine, glucuronide or sulfate conjugation. The metabolite resulting from reduction was found to be a molecule with a dithiol group, and the metabolite made by nitro reduction was found to be an aromatic amine corresponding to GN A. Both of these products may have pharmacological or toxicological activity, which is valuable information in terms of using GN A as a lead compound. In addition, this work showed that UPLC-QTOP-MS analysis coupled with efficient data processing programs is useful for rapid and reliable characterization of GN A metabolites in vivo. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 1-NITROPYRENE; MICROSOMES; MECHANISM; TOXICITY; TOXIN